Influence of Solar Wind on Secondary Cosmic Rays and Atmospheric Electricity - Chum, Jaroslav; Kollárik, Marek; Kolmašová, Ivana; Langer, Ronald; Rusz, Jan; Saxonbergová, Dana; Strhárský, Igor (Frontiers in Earth Science, 2021)
A relationship between the heliospheric magnetic field, atmospheric electric field, lightning activity, and secondary cosmic rays measured on the high mount of Lomnický Štít (2,634 m a.s.l.), Slovakia, during the declining phase of the solar cycle 24 is investigated with a focus on variations related to solar rotation (about 27 days). The secondary cosmic rays are detected using a neutron monitor and the detector system SEVAN, which distinguishes between different particles and energies. Using spectral analysis, we found distinct ∼27-day periodicities in variations of Bx and By components of the heliospheric magnetic field and in pressure-corrected measurements of secondary cosmic rays. The 27-day variations of secondary cosmic rays, on average, advanced and lagged the variations of Bx and By components by about 40° and −140°, respectively. Distinct 27-day periodicities were found both in the neutron monitor and the SEVAN upper and middle detector measurements. A nondominant periodicity of ∼27 days was also found for lightning activity. A cross-spectral analysis between fluctuation of the lightning activity and fluctuation of the heliospheric magnetic field (HMF) showed that fluctuation of the lightning activity was in phase and in antiphase with Bx and By components of the HMF, respectively, which is in agreement with previous studies investigating the influence of solar activity on lightning. On the other hand, the ∼27-day periodicity was not significant in the atmospheric electric field measured in Slovakia and Czechia. Therefore, no substantial influence of Bx and By on the atmospheric electric field was observed at these middle-latitude stations.